Smart Puzzle Team Media to Enhance Students’ Collaborative Attitudes - Sholehah, Ilmiyatus; Syamsudin; Zahroh, Ulfi Aminatuz (Jurnal al-Thullab, 2025)
Learning in elementary schools focuses on understanding the material and does not sufficiently involve collaborative student activities. Often, teachers present material that requires students to work in groups with their classmates, but this is unsuccessful. As a result, students' ability to cooperate and share roles is less than optimal. The solution provided by the researcher to overcome this problem is to use a learning medium called the Smart Puzzle Team. This research uses a descriptive qualitative method, which describes phenomena as they are scientifically by collecting data from interviews, observations, and collaborative attitude assessment sheets for students. This study aims to determine how the Deep Learning approach combined with the Smart Puzzle Team media, in this case, to shape students' collaborative attitudes, and what the results of the implementation are after using this media. The research results indicate that the integration between the deep learning approach and the Smart Puzzle Team learning media was successful in fostering students' collaborative attitudes at MI Al Fithrah Surabaya.